Axial involvement in psoriatic arthritis - E. E. Gubar; T. V. Korotaeva (Научно-практическая ревматология)
Among the variety of clinical manifestations of psoriatic arthritis (PsA) – including peripheral arthritis, dactylitis, enthesitis, and axial disease – spondylitis is the least studied. There is no generally accepted definition of axial PsA (axPsA), nor is there any common terminology or diagnostic criteria for it. In the rheumatology community, there is also no consensus regarding radiological and MRI assessment of axial involvement in PsA patients, while disease activity indexes and the therapeutic tactics are borrowed from those used in treating axial spondyloarthritis (axSpA) and ankylosing spondylitis (AS). However, despite a range of similarities in immunopathogenetic mechanisms of axPsA and axSpA, there are also certain differences that may affect the treatment response in these patients. The aim of this review is the analysis of data on axial disease in PsA. The article discusses the genetic features, clinical presentations, imaging techniques, differential diagnostics and treatment options of axPsA.